Strategi Pemasaran Syariah Bank Muamalat Indonesia - Tadjuddin Malik (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Bank Muamalat Indonesia as a business-oriented financial institution faces very tight competition among Islamic banks. Their marketed products are quite similar as those of other Islamic banks, the only difference is the socialization and marketing strategy of the products. The purpose of this scientific journal is obtaining the answer on how Bank Muamalat Indonesia the service to implement the socialization and marketing strategy of the products to the public. The research and the gather of data and information were carried out through conducting the interviews and observations on several customers. Document research through literature and the internet based on the concern of the concept of the Syariah Marketing Strategy of Bank Muamalat Indonesia. The data have been summarized, classified and analyzed using qualitative and quantitative methods. The results of how Bank Muamalat Indonesia provided information on the socialization and use of the concept of the Syariah Marketing Strategy to its customers showed that Bank Muamalat Indonesia still constrained by several factors that are inhibiting and cannot be overcome, such us the education and training for the syariah marketers personal, even though it has been known operating for about twenty years.